Acute Oral, Subacute, and Developmental Toxicity Profiling of Naphthalene 2-Yl, 2-Chloro, 5-Nitrobenzoate: Assessment Based on Stress Response, Toxicity, and Adverse Outcome Pathways - Anwar, Fareeha; Saleem, Uzma; rehman, Atta ur; Ahmad, Bashir; Ismail, Tariq; Mirza, Muhammad Usman; Ahmad, Sarfraz (Frontiers in Pharmacology, 2022)
U.S National research council (NRC) introduced new approaches to report toxicity studies. NRC vision is to explore the toxicity pathways leading to the adverse effects in intact organisms by the exposure of the chemicals. This study examines the toxicity profiling of the naphthalene-2-yl 2-chloro-5-dinitrobenzoate (SF5) by adopting the vision of NRC that move from traditional animal studies to the cellular pathways. Acute, subacute and developmental toxicity studies were assayed according to the Organization of economic cooperation and Development guidelines (OECD). Stress response pathway, toxicity pathway and adverse effects outcome parameters were analyzed by using their standard protocols. Results showed that acute toxicity study increases the liver enzyme levels. In a subacute toxicity study, alkaline Phosphatases (ALP) levels were raised in both male and female animals. SF5 significantly increases the normal sperm count in the male animals corresponding to a decrease in the abnormality count. Developmental toxicity showed the normal skeletal and morphological parameters, except little hydrocephalus was observed in developmental toxicity. In males, 20 mg/kg and in females, 4 mg/kg dose showed decreased glutathione (GSH) levels in the kidney and liver. MDA levels were also increased in the kidney and liver. However, histopathological studies did not show any cellular change in these organs. No statistical difference was observed in histamine levels, testosterone, nuclear factor erythroid two related factor-2 (Nrf2) and nuclear factor-kappa B (NF-κB), which showed no initiation of the stress response, toxicity, and adverse effects pathways. Immunomodulation was observed at low doses in subacute toxicity studies. It was concluded that SF5 did not produce abrupt and high toxicity levels in organs and biochemical parameters. So it will be safe for further studies.